2017
DOI: 10.1016/j.chemosphere.2017.02.121
|View full text |Cite
|
Sign up to set email alerts
|

Biochar provides a safe and value-added solution for hyperaccumulating plant disposal: A case study of Phytolacca acinosa Roxb. (Phytolaccaceae)

Abstract: In this work, an innovative approach using biochar technology for hyperaccumulator disposal was developed and evaluated. The heavy metal enriched P. acinosa biomass (PBM) was pyrolyzed to produce biochar (PBC). Both PBM and PBC were characterized with X-ray diffraction (XRD) for crystal phases, scanning electron microscopy (SEM) for surface topography, and analyzed for elemental composition and mobility. The results revealed that whewellite, a dominant crystal form in biomass, was decomposed to calcite after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The degrading effect of petroleum derivatives on soil causes a reduction in biodiversity, bioavailable forms of nitrogen and phosphorus and other elements and a violation of water and oxygen conditions (Obire and Nwabueta 2002;Souza et al 2014). Soaking the soil with oil derivatives can also affect on the uptake of particular nutrients by plants and their content in their organs (Wyszkowski et al 2004;Wang et al 2017), significantly reducing the uptake of macroelements (Borowik and Wyszkowska 2018). Wyszkowski and Ziółkowska (2009) demonstrated that diesel oil and petrol contribute to the reduction of nitrogen content in plants, which is consistent with the results of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The degrading effect of petroleum derivatives on soil causes a reduction in biodiversity, bioavailable forms of nitrogen and phosphorus and other elements and a violation of water and oxygen conditions (Obire and Nwabueta 2002;Souza et al 2014). Soaking the soil with oil derivatives can also affect on the uptake of particular nutrients by plants and their content in their organs (Wyszkowski et al 2004;Wang et al 2017), significantly reducing the uptake of macroelements (Borowik and Wyszkowska 2018). Wyszkowski and Ziółkowska (2009) demonstrated that diesel oil and petrol contribute to the reduction of nitrogen content in plants, which is consistent with the results of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, owing to MCWB biochar's environmental acceptability, it could be potentially exploited for further usability. In addition, Wang et al 139 and Cu et al 11 reported two different HMCWBs (Phytolacca acinosa and S. alf redii) and reported the highest sorption capacities by derived biochars for Cd (43.7−186.8 mg g −1 ), Cu (47.7 mg g −1 ), Pb (152−198.8 mg g −1 ), and Ag (198.3 mg g −1 ). Hence, biochars derived from MCWBs can be efficiently employed in wastewater treatment industries.…”
Section: Various Streams Of Products From Mcwbsmentioning
confidence: 99%
“…Potential physical and chemical effects caused by the presence of oils in soil are less oxygen supply, destructed soil structure and poor nutrient exchange. The other reported physical effects of oil’s presence in soils are the decrease in soil temperature and water holding capacity as well as the increase in soil pH that may linked with lower phosphorus availability (Wang et al 2017 ; Sonnleitner et al 2003 ). Many rhizoremediation investigations showed that weathered or aged contaminated soils showed less phytotoxic effects as compared to freshly spiked soils which yielded more plant biomass.…”
Section: Introductionmentioning
confidence: 99%